Effect of Genotype cum Compost-Fertilizer Combinations on Late Sown Wheat (Triticum aestivum L.) in Nepal - Tripathi, MP; Gautam, NR; Parajuli, BR; Bhattarai, MS; Upadhayay, SR; Chaudhary, S; Lama, C; Acharya, R; Chaudhary, M; Gyawali, P; Paneru, P; Subedi, P; et al. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A field experiment was carried out to investigate the growth and productivity of wheat cultivars by compost-fertilizer combination under late sown condition at agronomy farm of Agriculture and Forestry University, Rampur in 2014. The purpose of this research was to identify amount of fertilizer and/or manure combination to achieve better yield performance on late sown wheat in Chitwan. Experiment laid out in split plot design with three replications considering four levels of fertilizer or manure combination as main plot factor and five wheat genotypes as the sub-plot factor while net plot size was 4x3 m2. Effect of genotype and genotype x compost-fertilizer interaction was nonsignificant for grain yield. However, the ½ compost: ½ fertilizer combinations produced significantly higher grain yield than the 100% complete fertilizer and/or 100% manure. The synergistic response of the compost-fertilizer combinations may have contributed for the greater yield of wheat genotypes. This experiment clearly demonstrated the importance of compost-fertilizer combination on grain yield of wheat under late sown condition.